Investor reaction to the disclosure of financial impact of sustainability: The moderating role of investor type - Du, Mengjiao Nancy; Wong-On-Wing, Bernard (Accounting, Organizations and Society, 2026)
We examine the effect of disclosing the potential financial impact of sustainability activities (FISA) on investor decisions. We posit and find that the effect is moderated by both companies' financial condition and investors' view on sustainability. Our results suggest that investors with a stakeholder value-maximization view are not sensitive to the FISA disclosure regardless of the company's financial condition. However, investors holding a shareholder expense view exhibit significantly higher investment interest in the presence of a FISA disclosure when the company's financial condition is favorable, but not when it is unfavorable. Additional analysis suggests that the presence of FISA leads to differential belief updates for investors with different ex-ante beliefs about the benefits of sustainability. Our study provides practical insights into the effect of disclosing the financial effects of sustainability activities. It has implications for integrated reporting and the disclosure of the connectivity between sustainability and financial performance proposed by standard setters. It also contributes to the literature on the relevance of non-financial information and investor type to investment decisions.